Dry Arthroscopic Hip Labral Repair to Minimize Use of Irrigation Fluid - Jason G. Ina, M.D.; Austen L. Thompson, M.D.; Brandon C. Cabarcas, M.D.; Aaron J. Krych, M.D.; Mario Hevesi, M.D., Ph.D. (Arthroscopy Techniques)
Hip arthroscopy is a technically demanding procedure that can require a substantial volume of irrigation fluid. Techniques should be explored to optimize fluid use while ensuring satisfactory surgical instrumentation and labral repair. In this technical note, we present a method for performing a dry arthroscopic labral repair. This technique can be used in the treatment of a variety of labral pathologies, including primary labral repair with knotless or hand-tied anchors, revision labral repair, and labral reconstruction, without the need for irrigation fluid. Additionally, we discuss supplemental techniques that can be used during other portions of the arthroscopic hip procedure to limit irrigation fluid use.